Artemisinin and artemisinin derivatives as anti-fibrotic therapeutics - David Dolivo; Pamela Weathers; Tanja Dominko (Elsevier, 2021)
Fibrosis is a pathological reparative process that can occur in most organs and is responsible for nearly half of deaths in the developed world. Despite considerable research, few therapies have proven effective and been approved clinically for treatment of fibrosis. Artemisinin compounds are best known as antimalarial therapeutics, but they also demonstrate antiparasitic, antibacterial, anticancer, and anti-fibrotic effects. Here we summarize literature describing anti-fibrotic effects of artemisinin compounds in in vivo and in vitro models of tissue fibrosis, and we describe the likely mechanisms by which artemisinin compounds appear to inhibit cellular and tissue processes that lead to fibrosis. To consider alternative routes of administration of artemisinin for treatment of internal organ fibrosis, we also discuss the potential for more direct oral delivery of Artemisia plant material to enhance bioavailability and efficacy of artemisinin compared to administration of purified artemisinin drugs at comparable doses. It is our hope that greater understanding of the broad anti-fibrotic effects of artemisinin drugs will enable and promote their use as therapeutics for treatment of fibrotic diseases.